Triple Threat: Significant Concomitant Aortic Stenosis, Mitral Stenosis, and Systolic Anterior Motion of the Mitral Valve Causing Left Ventricular Outflow Tract Obstruction in Cardiac Surgical Patients. (17th March 2023) - Glines, Katelyn; Hayanga, J. W. Awori; Gibson, Christina; El Churafa, Mohamad; Wei, Lawrence; Hayanga, Heather K.
Abstract : Systolic anterior motion (SAM) describes a pathologic condition of the mitral valve in which the anterior leaflet is displaced anteriorly, resulting in a narrowed left ventricular outflow tract (LVOT). The implications of SAM may range in severity from clinically insignificant disease to severe LVOT obstruction resulting in hemodynamic collapse. While SAM is typically observed in patients with hypertrophic cardiomyopathy or following mitral valve repair, it may be seen in any setting in which the anatomy and function of the left ventricle has been altered. Here we discuss two patients who presented for aortic and mitral valve replacements for concomitant aortic and mitral stenosis. These cases were further complicated by the preoperative diagnosis of SAM in addition to the preexisting valvular lesions, further increasing the risk of sudden hemodynamic collapse and cardiac arrest.